Electro chemical response of stir zone in friction stir welded AA7075-T651 joint in sodium chloride solution. (2020) - Prabhuraj, P.; Rajakumar, S.; Balasubramanian, V.
Abstract: High strength heat treatable aluminium alloy AA7075T-651 is widely used in aircraft industries. It is very difficult to weld in fusion technique due to poor solidification and microstructure in weld region. Friction Stir Welding is reliable technique to joining aluminium alloys in solid state condition with sound weld ability. In this work, rolled aluminium plate with thickness of 10 mm were square butt welded by Friction Stir Welding (FSW) process. The electrochemical corrosion behavior of FSW joints were investigated in 3.5% wt NaCl solution. The corrosion morphology of friction stir zone has been compared with parent metal. It is observed that, stir zone prone more corrosion potential than parent metal.